Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jacc.2015.03.557
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic Atrial Cardiomyopathy, Atrial Fibrillation, and Thromboembolism

Abstract: The association of atrial fibrillation (AF) with ischemic stroke has long been recognized; yet, the pathogenic mechanisms underlying this relationship are incompletely understood. Clinical schemas, such as the CHA2DS2-VASc (congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, stroke/transient ischemic attack, vascular disease, age 65 to 74 years, sex category) score, incompletely account for thromboembolic risk, and emerging evidence suggests that stroke can occur in patients with AF even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(150 citation statements)
references
References 120 publications
1
133
1
9
Order By: Relevance
“…In our study, neither suPAR nor hsCRP levels correlated with the volume of infarction measured from brain computed tomography. We found no association between the incidence of AF and the suPAR levels during the 5-year follow-up, although an inflammatory mechanism has been suggested to be a pathogenic factor behind atrial arrhythmias (33,34). The causal relationship between suPAR and all-cause mortality remains to be clarified.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, neither suPAR nor hsCRP levels correlated with the volume of infarction measured from brain computed tomography. We found no association between the incidence of AF and the suPAR levels during the 5-year follow-up, although an inflammatory mechanism has been suggested to be a pathogenic factor behind atrial arrhythmias (33,34). The causal relationship between suPAR and all-cause mortality remains to be clarified.…”
Section: Discussioncontrasting
confidence: 56%
“…Subsequently, several observations have suggested that additional mechanisms may be at work when considering AF as a marker of risk, for not only stroke, but a wide range of vascular outcomes. (8) A large meta-analysis involving over half a million patients with AF over a median follow-up period ranging from 3 -6 years, highlights that this arrhythmia is associated with increased absolute risk of heart failure (11.1 events/1 000 person-years), chronic kidney disease (6.6/1 000), stroke (3.6/1 000) and ischaemic heart disease (1.4/1 000) as well as excess cardiovascular (2.6/1 000) and all-cause mortality (3.8/1 000). (9) Certainly this association does not imply direct causality but it does question why a correlation with excess mortality and morbidity from both cardiovascular and non-cardiovascular causes exists.…”
Section: Atrial Fibrillation As a Vascular Diseasementioning
confidence: 99%
“…Atrial myocyte apoptosis leads to activation of fibroblasts via several mediators (including calpain, angiotensin II and transforming growth factor beta-1) resulting in collagen deposition and fibrosis. (8) Genomic studies have also identified genetic variants associated with a susceptibility for primary atrial fibrosis. (10) Atrial fibrosis disrupts diastolic function and electrical conduction.…”
Section: Atrial Fibrillation As a Vascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] The ablation of these 'fibrotic atrial' forms of AF often requires adjunctive strategies targeting the abnormal LA substrate, such as linear LA ablation with the goal of compartmentalising the LA into smaller regions incapable of sustaining micro re-entry, or the ablation of complex fractionated atrial electrograms (CFAEs, or areas of abnormal substrate representing areas of slow conduction, conduction block or local 'pivot' points) that perpetuate AF re-entry. 20,[30][31][32][33] However, the addition of such substrate-based ablation (either linear ablation or CFAE elimination) does not appear to reduce AF recurrence after PVI in patients with persistent AF. 34 It has been suggested that ganglionated plexi may have a role in the initiation and maintenance of both paroxysmal and non-paroxysmal AF.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%